SHORT TERM EFFECTIVENESS OF LEFLUNOMIDE IN THE TREATMENT OF ACTIVE RHEUMATOID ARTHRITIS - Taqweem, Amjad; Ahmed, Ibrar; ., Nowsherwan; Ali, Zafar; Mehboob, Amjad (Journal of Postgraduate Medical Institute, 2011)
Objective: TO measure the effectiveness of 6 months treatment with leflunomide in patients with active rheumatoid arthritis.